Improving the diversity of resistance mechanisms available in wheat to combat Fusarium Ear Blight disease - Holdgate, Sarah (Cranfield University, 2009)
Fusarium ear blight (FEB) is a disease of wheat and small grain cereals, caused by the fungi Fusarium culmorum and Fusarium graminearum. The disease causes premature bleaching of spikelets and shrivelling of the grain can result in a direct yield loss. Mycotoxins such as deoxynivalenol produced by the fungus can reduce grain quality. Breeding for resistant wheat cultivars is considered one of the best control options. Previously identified resistance has been reported in the Chinese genotype Sumai 3. The principal aim of this project was to identify novel sources of resistance to FEB. Twenty four wheat genotypes were evaluated for resistance to FEB in this project. Molecular markers linked to previously identified QTL from Sumai 3 conferring resistance were used to confirm their absence in the genotypes under investigation, and revealed that none of the genotypes under investigation contained all of the QTL for resistance. Field trials conducted over two years screening for resistance demonstrated that, although not statistically similar to Sumai 3, levels of disease were below 10% in some of the Chinese genotypes. Follow up experiments using reporter strains of Fusarium graminearum explored the accumulation of fungal biomass and the expression of the gene Tri5, which is essential for DON biosynthesis. Fungal biomass levels were not significantly different between genotypes; however expression of the Tri5 gene was significantly lower in the genotype Alsen. A previously developed wheat leaf seedling bioassay was also explored. Scanning electron microscopy revealed the presence of fungal hyphae in advance of the visible lesion during the infection course of F. culmorum. Inoculation with a Tri5 mutant strain of F. graminearum demonstrated that a lack of mycotoxin production altered the lesion type. This project has successfully identified potential novel resistance mechanisms and the future prospects for the control of this disease are discussed.